SCIENCE EDUCATION PROGRAMS IN THE DEVELOPING COUNTRIES OF SOUTH AND SOUTHEAST ASIA. - Koelsche, Charles L. (Science Education, 1964)
The article focuses on science education programs in secondary schools of the developing countries namely, Pakistan, India, Burma and Thailand. Science programs in the secondary schools under study varied from all the way from no courses to the usual four courses found in the U.S. Physical science is taught more frequently. Simple physical and biological science facts is introduced in grades 5 to 7, while general science appears in grades 8, 9 and 10 which consists primarily of physics and chemistry. Classical topics such as mechanics, heat, light and electricity and magnetism make up the subject matter covered in physics. Teaching methods are based on the principle of memorizing facts, theories and laws in order to reproduce them on examinations. English has been the predominant language used for science instruction at the high schools, intermediate and teachers colleges and universities in the South and Southeast Asian countries.